PENINGKATAN PENGETAHUAN IBU DAN PENILAIAN TUMBUH KEMBANG BALITA DI KELURAHAN KORONG GADANG KECAMATAN KURANJI KOTA PADANG - Resmiati Resmiati; Fivi Melva Diana; Rifda Shofiyyah; Rohani Azizah Matondang; Muhammad Arif Saputra; Nasywa Maulida Samudra; Dwi Putri Aprillia; Moza Orvala Alvissia (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Stunting represents a critical public health issue that significantly impairs children's growth and development, particularly during the golden window of the first 1,000 days of life. One of the major contributing factors to the high prevalence of stunting in Indonesia is the limited maternal knowledge and inadequate early detection of child development. This community engagement initiative aimed to enhance maternal awareness regarding stunting prevention and to conduct early developmental screening using the Pre-Screening Developmental Questionnaire (Kuesioner Pra-Skrining Perkembangan/KPSP) at community health posts (Posyandu) in RW 8, 9, and 10 of Korong Gadang Sub-district, Padang City. The methods employed included health education through interactive discussions supported by leaflets, assessment of maternal knowledge via pre-test and post-test questionnaires, and developmental observation of children using the KPSP tool. The target participants were mothers of children under five years of age. The results indicated a significant increase in maternal knowledge, with the average score rising from 79.7 in the pre-test to 86.5 in the post-test. Additionally, early developmental screening revealed that the majority of children were within the age-appropriate development category. The findings suggest that nutrition and health education can effectively enhance maternal knowledge and support stunting prevention at the community level. Furthermore, the educational intervention demonstrated a positive impact on stunting prevention and the optimisation of child growth and development.